Submarine films as narratives of masculinity - MacDonald, Alex (2002)
The research for this thesis is on representations of masculinity in Anglo-American submarine films since 1943. The discussion will draw on relevant work on the representation of masculinity and popular cinema in film and cultural studies. In particular, the thesis will account for the notion of hegemony in relation to masculinity in the submarine film. Further, the notion of hegemonic masculinity will be addressed in terms of four key claims. These are as follows: that relations between groups are characterised solely by domination and subordination, that a singular hegemonic masculinity prevails at anyone time, that this masculinity is coherent, and that hegemonic masculinity is consistently dominant in relations of power.